356 ALTERED PATTERNS OF B CELL DEVELOPMENT IN MRL AND C57BL/6 sle1, sle2, sle3 CONGENIC MICE SUGGEST ABNORMAL REGULATION OF EARLY- AND LATE-STAGE REPERTOIRE CHECKPOINTS MAY CONTRIBUTE TO AN AUTOIMMUNE DIATHESIS. (1st January 2005) - Farazmand, M.; Kapoor, P.; Wakeland, E. K.; Mohan, C.; Schroeder, H. W.
Abstract : We sought to test whether antibody repertoire development is abnormally regulated in mice that are genetically susceptible to the development of autoimmune disease. We have previously generated a transgenic strain of BALB/c mice whose DH locus has been altered to force use of amino acids from the inverted reading frame of the DSP2.2 gene segment. This sequence contains Arg, His, and Asn. The transgenic IgHa DH allele is termed Δ-iD, for deleted DH locus with a single, inverted D gene segment. On a BALB/c background, these mice evidence two partial blocks in B cell development. The first occurs in the bone marrow in the transition from the early to the late pre-B cell stage (Hardy Fraction C to D). Transition through this checkpoint requires the H chain to successfully create a pre-B cell receptor. The second occurs in the periphery, in the transition from the immature, transitional B cell to the follicular cell stage. These blocks are associated with progressive selection for a less highly charged CDR-H3 repertoire. We backcrossed the Δ-iD allele for ten generations to MRL and for seven generations to C57BL/6. The latter were then crossed with C57BL/6 mice congenic for three intervals derived from the autoimmune NZM2410 strain. Evaluation of B cell development in C57BL/6 by FACS revealed a similar block in development in the bone marrow in the transition from Fraction C to D, but no further loss in absolute B cell numbers was observed in the periphery. A similar pattern was observed in the sle1 congenic strain. The early block in development was also observed in the sle2 and sle3 congenic strains, but unlike controls the absolute number of follicular cells normalized in these latter strains. On an MRL background, no blocks in B cell development were observed. These results suggest that the sle2 and sle3 susceptibility loci have altered late-stage repertoire development, whereas repertoire development may be abnormal both centrally and peripherally in MRL.